2009
DOI: 10.1007/s00125-009-1555-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell division autoantigen 1 plays a profibrotic role by modulating downstream signalling of TGF-β in a murine diabetic model of atherosclerosis

Abstract: CDA1 plays an important role in vascular ECM accumulation by amplifying TGF-beta signalling. This is critical for the profibrotic effect of TGF-beta in the vasculature. CDA1 is therefore a potential target for attenuating vascular ECM accumulation caused by enhanced TGF-beta action, as seen in diabetic atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 41 publications
5
46
0
Order By: Relevance
“…19 CDA1 knockdown by siRNA not only attenuates TGF-b-stimulated Smad3 (mothers against decapentaplegic homolog 3) phosphorylation and transcriptional activities but also ultimately blocks the stimulated expression of TGF-b target genes in association with fibrogenesis, such as connective tissue growth factor (CTGF), collagens, and fibronectin. 19,20 These findings support the hypothesis that CDA1 is a potential molecular target for retarding the pathologic activities of TGF-b and renal scarring in diabetes.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…19 CDA1 knockdown by siRNA not only attenuates TGF-b-stimulated Smad3 (mothers against decapentaplegic homolog 3) phosphorylation and transcriptional activities but also ultimately blocks the stimulated expression of TGF-b target genes in association with fibrogenesis, such as connective tissue growth factor (CTGF), collagens, and fibronectin. 19,20 These findings support the hypothesis that CDA1 is a potential molecular target for retarding the pathologic activities of TGF-b and renal scarring in diabetes.…”
supporting
confidence: 71%
“…Signaling Pathways In Vivo Involving Smad3 and Extracellular Signal-Regulated Kinase MitogenActivated Protein Kinase in Mouse Kidney Because CDA1 seems to play a significant role in enhancing TGF-b signaling in vitro, 19,20 it was hypothesized that the diabetes-induced activation of TGF-b signaling pathways, including Smad3 and extracellular signal-regulated kinase 1/2(p44/42) [ERK1/2(p44/42)] mitogen-activated protein kinase, would be attenuated in CDA1 KO mice. To examine this postulate, we assessed the activated form of Smad3 in the kidneys of these mice by immunohistochemical staining using an antibody specific for phospho-Smad3 (Ser 423/425 ).…”
Section: Cda1 Deficiency Attenuates Tgf-b-associatedmentioning
confidence: 99%
“…Since TSPYL2 had been associated with the pro-fibrotic role of TGFβ in diabetic atherosclerosis and diabetic retinopathy, [13][14][15] we tested whether TSPYL2 could affect TGFβ-driven phenotypes in our cancer cell systems. TGFβ is known to induce proliferation arrest in primary epithelial cells of various organs and the TGFβ pathway is frequently deregulated in malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…Catechin beneficially impacts many of these parameters including vascular dysfunction, including lipoprotein oxidation, blood platelet aggregation, vascular inflammation, vascular smooth muscle cell (VSMC) proliferation, altered lipid profile and vascular reactivity. Besides being antioxidants, catechins exert biological effects by modulating some cellular signaling pathways that lead to a reduction in inflammation, platelet aggregation, and an elevation of vascular reactivity [29]. The sources for the reactive oxygen species (ROS) production during CVD are uncoupling of mitochondrial electron transport, pro-inflammatory cytokines and induction of oxidative enzymes such as inducible nitric oxide synthase (iNOS) and xanthine oxidase (XO) [30].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena of endothelial dysfunction, mostly reduced availability of NO but also other factors, is widely associated with the pathogenesis and the precipitation of the clinical manifestations of CVDs. Experimental and clinical studies have shown that catechins improve endothelial function [29]. Quercetin is a naturally occurring flavonoid that exerts multiple pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%